A-Kinase Interacting Protein 1 Knockdown Restores Chemosensitivity via Inactivating PI3K/AKT and β-Catenin Pathways in Anaplastic Thyroid Carcinoma - Zheng, Haiyan; Lin, Qingyuan; Rao, Yamin (Frontiers in Oncology, 2022)
Background: A-kinase interacting protein 1 (AKIP1) promotes tumor progression and chemoresistance in several malignancies; meanwhile, it is related to higher tumor size and recurrence risk of papillary thyroid carcinoma. While the role of AKIP1 in anaplastic thyroid carcinoma (ATC) is unclear. This study aimed to explore the effect of AKIP1 knockdown on cell malignant behaviors and doxorubicin resistance in ATC. Methods: AKIP1 knockdown was conducted in ATC cell lines (8505C and CAL-62 cells) by siRNA; then cell viability, apoptosis, invasion, PI3K/AKT and β-catenin pathways, doxorubicin sensitivity were detected. Subsequently, doxorubicin-resistant 8505C cells (8505C/Dox) were established. Additionally, AKIP1 was modified in 8505C and 8505C/Dox cells underwent doxorubicin treatment by siRNA or overexpression plasmid, followed by cellular function and pathway detection. Results: AKIP1 was elevated in FRO, 8505C, CAL-62 and KHM-5M cells compared to control cells (all P<0.05). Subsequently, AKIP1 knockdown elevated apoptosis, inhibited viability, invasion, and inactivated PI3K/AKT and β-catenin pathways in 8505C and CAL-62 cells (all P<0.05). AKIP1 knockdown decreased relative cell viability in doxorubicin-treated 8505C and CAL-62 cells; then AKIP1 was elevated in 8505C/Dox cells compared to 8505C cells (all P<0.05). Furthermore, AKIP1 knockdown restored doxorubicin sensitivity (reflected by decreased cell viability and invasion, increased apoptosis), but inactivated PI3K/AKT and β-catenin pathways in doxorubicin-treated 8505C/Dox cells. However, AKIP1 overexpression presented opposite effect on these functions and pathways in doxorubicin-treated 8505C cells. Conclusion: AKIP1 knockdown decreases cell survival and invasion while promotes sensitivity to doxorubicin via inactivating PI3K/AKT and β-catenin pathways in ATC.